Bridging Technology and Geography: Contextual E-Comics for Enhanced Learning in Indonesian Natural Resource Management - Nur Fitri Andarukmi; Sumarmi; Fatiya Rosyida; Yusuf Suharto; Syazwani Binti Sazali; Lai Chin Wei (CV Bumi Spasial, 2024)
This study explores the development of innovative digital learning media in geography education during the COVID-19 pandemic. It uses contextual e-comics to help people learn more about Indonesian natural resource management. These were made through a research and development process that used the ADDIE model, which stands for Analysis, Design, Development, Implementation, and Evaluation. The final product is a contextual E-Comic in PDF format designed to enhance learning in geography. Feasibility and effectiveness were vital evaluation metrics. Validation by media, subject matter experts, and linguists yielded approval ratings of 96%, 71%, and 92%, respectively. Student trials showed an 89% acceptance rate, and teacher feedback indicated a 92% approval rating. An important finding was that the E-Comic worked, as demonstrated by a paired sample t-test with a significant t-value of 0.000. This indicates that it could be a valuable educational tool during the pandemic. This study addresses the challenges of geography education during a global health crisis and showcases the potential of digital media to enhance learning experiences.